From Cultural Heritage to Ethical Obligations: Rethinking Animal Shows in Jurisprudence - Tedjabuwana, Rosa; Arifin, Firdaus; Adriansyah, Rian Nurul (Universitas Sang Bumi Ruwa Jurai, 2025)
This paper explores the tension between the preservation of cultural heritage and the growing ethical obligations toward animal welfare, with a focus on animal shows as a site of conflict. Rooted in longstanding traditions, animal shows often carry significant cultural and historical value, serving as expressions of communal identity and continuity. However, they also raise profound ethical concerns regarding the treatment and welfare of animals, particularly when practices involve cruelty or exploitation for human entertainment. Adopting a jurisprudential perspective, the paper critically examines how legal systems navigate this tension. It analyses the extent to which laws accommodate cultural traditions while addressing moral imperatives to protect sentient beings. Through case studies from various jurisdictions, the study evaluates legal frameworks that attempt to balance cultural relativism with universal principles of animal rights. Drawing on theories of legal pluralism, cultural relativism, and utilitarian ethics—particularly Peter Singer’s principle of equal consideration—the paper interrogates the adequacy of existing regulatory mechanisms and the moral underpinnings of legal decisions. The analysis culminates in a call for rethinking jurisprudential approaches to animal shows, advocating for legal reforms that harmonize cultural preservation with ethical progress. By proposing pathways for integrating cultural sensitivity with animal welfare protections, this paper seeks to contribute to a more compassionate and equitable legal landscape that respects both human heritage and nonhuman sentience